2022
DOI: 10.3138/canlivj-2021-0031
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to hepatitis C testing in two First Nations communities of northwest Ontario

Abstract: BACKGROUND: Two remote First Nations communities each collaborated with an urban-based liver clinic to organize wide-spread testing, followed by linkage to care for hepatitis C virus (HCV). METHOD: Involvement of community members was central to planning and conduct of the programs. Samples were obtained using dry blood spot cards (DBS). A week-long pilot study in Community 1 investigated the effectiveness of the program, using DBS. Community 2, being larger, more remote, and known to be endemic for HCV was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…Participants described how having community members modelling getting tested, and hosting DBST at Métis community events may reduce the stigma associated with HIV/STBBI testing and improve awareness of HIV/STBBI in Métis communities. Similarly, preliminary research in First Nations communities has suggested that a community-level DBS intervention may improve levels of STBBI knowledge and awareness [22]. Additionally, in line with our findings, stigma has been identified in the literature as a barrier to STBBI testing for a variety of populations [12,39].…”
Section: Reducing Stigma and Increasing Awarenesssupporting
confidence: 88%
See 4 more Smart Citations
“…Participants described how having community members modelling getting tested, and hosting DBST at Métis community events may reduce the stigma associated with HIV/STBBI testing and improve awareness of HIV/STBBI in Métis communities. Similarly, preliminary research in First Nations communities has suggested that a community-level DBS intervention may improve levels of STBBI knowledge and awareness [22]. Additionally, in line with our findings, stigma has been identified in the literature as a barrier to STBBI testing for a variety of populations [12,39].…”
Section: Reducing Stigma and Increasing Awarenesssupporting
confidence: 88%
“…Both providers and recipients described the DBST process as easy: it was easy to get tested and it was easy to have community members be trained to administer DBST. Our findings regarding the ease and simplicity of the DBST process are corroborated by existing research, which has shown that DBST is straightforward enough for individuals to provide self-collected samples and may lead to increase in STBBI testing [22,35]. Additionally, portability was seen as a beneficial quality, contributing to the "ease" of DBST, by both DBST providers and recipients, and was identified by participants as a strategy for increasing STBBI testing rates and accessibility for Métis community members in rural/remote areas.…”
Section: Acceptability Of Dbstsupporting
confidence: 85%
See 3 more Smart Citations